Cardiac procedural myocardial injury, infarction, and mortality in patients undergoing elective percutaneous coronary intervention: a pooled analysis of patient-level data. (30th November 2020) - Silvain, Johanne; Zeitouni, Michel; Paradies, Valeria; Zheng, Huili L; Ndrepepa, Gjin; Cavallini, Claudio; Feldman, Dimitri N; Sharma, Samin K; Mehilli, Julinda; Gili, Sebastiano; Barbato, Emanuele; Tarantini, Giuseppe; et al.
Abstract: Aims: The prognostic importance of cardiac procedural myocardial injury and myocardial infarction (MI) in chronic coronary syndrome (CCS) patients undergoing elective percutaneous coronary intervention (PCI) is still debated. Methods and results: We analysed individual data of 9081 patients undergoing elective PCI with normal pre-PCI baseline cardiac troponin (cTn) levels. Multivariate models evaluated the association between post-PCI elevations in cTn and 1-year mortality, while an interval analysis evaluated the impact of the size of the myocardial injury on mortality. Our analysis was performed in the overall population and also according to the type of cTn used [52.0% had high-sensitivity cTn (hs-cTn)]. Procedural myocardial injury, as defined by the Fourth Universal Definition of MI (UDMI) [post-PCI cTn elevation ≥1 × 99th percentile upper reference limit (URL)], occurred in 52.8% of patients and was not associated with 1-year mortality [adj odds ratio (OR), 1.35, 95% confidence interval (CI) (0.84–1.77), P  = 0.21]. The association between post-PCI cTn elevation and 1-year mortality was significant starting ≥3 × 99th percentile URL. Major myocardial injury defined by post-PCI ≥5 × 99th percentile URL occurred in 18.2% of patients and was associated with a two-fold increase in the adjusted odds of 1-year mortality [2.29, 95% CI (1.32–3.97), P  = 0.004]. In the subset of patients for whom periprocedural evidence of ischaemia was collected ( n  = 2316), Type 4a MI defined by the Fourth UDMI occurred in 12.7% of patients and was strongly associated with 1-year mortality [adj OR 3.21, 95% CI (1.42–7.27), P  = 0.005]. We also present our results according to the type of troponin used (hs-cTn or conventional troponin). Conclusion: Our analysis has demonstrated that in CCS patients with normal baseline cTn levels, the post-PCI cTn elevation of ≥5 × 99th percentile URL used to define Type 4a MI is associated with 1-year mortality and could be used to detect 'major' procedural myocardial injury in the absence of procedural complications or evidence of new myocardial ischaemia. Graphical Abstract: